دور تكنولوجيا المعلومات و الاتصال في تحسين الاتصال الداخلي في المؤسسات الاستشفائية العمومية الجزائرية - دراسة حالة مستشفى محمد بوضياف بورقلة الجزائر – - كاوج, أ /بشير; شريفة, د/ رفاع (Sciences humaines, 2016)
تهدف هذه الدراسة إلى التعرف عن دور تكنولوجيا المعلومات و الإتصال في تحسين الإتصال الداخلي في المؤسسات الإستشفائية العمومية الجزائرية. يتكون مجتمع الدراسة المستهدف        من العمال التابعين للطاقم الإداري و الطبي ،   و إستخدم الباحثون طريقة العينة العشوائية البسيطة و التي بلغ حجمها 43 عامل و عاملة، ولتحقيق أهداف الدراسة تم تصميم إستبيان مكون من (23) فقرة، و المقابلة مع أصحاب القرار في المؤسسة كأدوات لجمع البيانات الأولية . و توصلت الدراسة إلى عدة نتائج أهمها:  أن الهدف الرئيسي لإدخال تكنولوجيا(TIC)  في المستشفى هو توفيرالرعاية الحقيقية للمرضى، و كذلك أن إدماج (TIC)في وظائف مختلفة من المستشفى لا يسمح بالسرعة      في معالجة المعلومات فقط ولكن أيضا تخفيض التكاليف وكذا تحسين صورة المستشفى،      و زيادة التنسيق داخل أجزاء المؤسسة        و متابعة الأزمات و الأوبئة. تهدف هذه الدراسة إلى التعرف عن دور تكنولوجيا المعلومات و الإتصال في تحسين الإتصال الداخلي في This study aims to identify the role of information and communication technology (ICT) in the improvement of the internal communication at the Algerian public hospitals. The target population of the study consists of administrative staff and medical staff, at  M ed Boudiaf  public hospital in Ouargla, the researchers used simple random sample method and a volume of (43) workers, in order to achieve the objectives of the study the researchers designed a questionnaire consisting of (23) paragraphs, and interview with the decision-makers in the organization to gather the primary data. This study concluded that several of the most important results: The main objective of using  (ICT) inside hospital to provide real patient care.               aswell as the integration of (ICT) in the different functions of the hospital it doesn't allow the speed in processing information only but also decrease costs ,and  improve the image of the hospital , increase coordination within the parts of the institution and the follow-up crises and epidemics.